2021
DOI: 10.3390/nu13093283
|View full text |Cite
|
Sign up to set email alerts
|

From Diospyros kaki L. (Persimmon) Phytochemical Profile and Health Impact to New Product Perspectives and Waste Valorization

Abstract: Persimmon (Diospyros kaki L.) fruit’s phytochemical profile includes carotenoids, proanthocyanidins, and gallic acid among other phenolic compounds and vitamins. A huge antioxidant potential is present given this richness in antioxidant compounds. These bioactive compounds impact on health benefits. The intersection of nutrition and sustainability, the key idea behind the EAT-Lancet Commission, which could improve human health and decrease the global impact of food-related health conditions such as cancer, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 213 publications
(308 reference statements)
0
21
1
Order By: Relevance
“…In Japan, calyces are utilized in the folk system for the use of high cough [ 5 ]. D. kaki various parts contain several bioactive compounds which include; tannins, flavonoids, steroids, carotenoids, naphthoquinones, steroids, sugars, lipids, and amino acids [ [6] , [7] , [8] ]. The major phytochemical isolated from D. kaki is plumbagin which has been documented for excellent insecticidal, sterilant, and antifeedant activities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, calyces are utilized in the folk system for the use of high cough [ 5 ]. D. kaki various parts contain several bioactive compounds which include; tannins, flavonoids, steroids, carotenoids, naphthoquinones, steroids, sugars, lipids, and amino acids [ [6] , [7] , [8] ]. The major phytochemical isolated from D. kaki is plumbagin which has been documented for excellent insecticidal, sterilant, and antifeedant activities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…(The extract and isolated compound of D. Kaki has been documented for excellent analgesic, sedative, and anti-inflammatory effects [ 19 , 20 ]. (Persimmon fruits are a rich source of proanthocyanidins, gallic acids, vitamins, and other phenolic compounds, which have excellent antioxidant activity [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. The chloroform extract and isolated compounds from D. kaki have reported excellent insecticidal effects [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Persimmons fruits are a good source of carotenoids, mostly found in skin and flesh, which are responsible for the color of the fruits and whose amount increases as the fruit ripens [40,41]. Zhou et al [42], showed that β-cryptoxanthin was the most abundant carotenoid among all individual components in both peel and flesh.…”
Section: Carotenoids Contentmentioning
confidence: 99%
“…Flavonoids produced by plants have many health benefits for humans and play crucial roles in both the fruit quality and its economic value (Dias et al, 2021;Xie et al, 2022). Persimmons are rich in phytochemicals such as flavonoids, carotenoids, triterpenoids, fatty acids, and vitamin C (Direito et al, 2021), with flavonoids being the main active antioxidants (Sun et al, 2011). The persimmon fruit has a variety of pharmacological poroperties, including antiadipogenic, hypocholesterolemic, antioxidant, anti-inflammatory, and antitumor poroperties, due to its flavonoid components such as hesperidin, naringin, and nobiletin (Direito et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Persimmons are rich in phytochemicals such as flavonoids, carotenoids, triterpenoids, fatty acids, and vitamin C (Direito et al, 2021), with flavonoids being the main active antioxidants (Sun et al, 2011). The persimmon fruit has a variety of pharmacological poroperties, including antiadipogenic, hypocholesterolemic, antioxidant, anti-inflammatory, and antitumor poroperties, due to its flavonoid components such as hesperidin, naringin, and nobiletin (Direito et al, 2021). Besides, flavonoids such as proanthocyanidins are associated with the astringency and flavor of the persimmon fruits (Zheng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%